Perlindungan Hukum Bagi Pemilik Merek Dagang Atas Penjualan Barang Palsu pada Platform Marketplace - Bernadetta Lakshita Pradipta Utomo; Sudaryat Sudaryat; Aam Suryamah (Universitas Batanghari Jambi, 2021)
Nowadays technology changes is more advanced. One of the changes caused by the development of information technology is human behavior in realizing the results of their intellectual property. We can view intellectual property through online platforms easily. The Covid-19 pandemic has caused the sale of goods that were offline becomes online. Other than that, there are also a lot of counterfeit goods which has peaked on the marketplace platform. This research aims to gain an understanding of legal protection for brand owners and about legal actions that can be taken by them for selling counterfeit goods on the marketplace platform. The research method used is normative juridical. The results of this study are based on Law no. 20 of 2016 concerning on Marks and GI and Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 on EIT in order to obtain more comprehensive protection, trademark owners must first register their trademarks. In addition, efforts that can be made by trademark owners are taking actions such as making complaints to each marketplace platform, resolving alternative disputes, submitting requests for provisional decisions, civil lawsuits by requesting compensation, and criminal sanctions.